Комплексное использование некондиционного нефрита - Худякова Л. И. Людмила Ивановна; Кислов Е. В. Евгений Владимирович; Палеев П. Л. Павел Леонидович; Малышев А. В. Алексей Владимирович (2020, 2020)
Заглавие с титульного листа